Ocena wpływu obozu pierwszego stopnia Aktywnej Rehabilitacji na jakość życia osób po uszkodzeniu rdzenia kręgowego w zależności od poziomu uszkodzenia rdzenia kręgowego - Kamińska-Gwóźdź, Ewelina; Lewicki, Romuald; Studnicki, Rafał; Szłapińska, Joanna; Kubicki, Jacek; Włoch, Anna; Opuchlik, Anna (Journal of Education, Health and Sport, 2015)
Kamińska-Gwóźdź Ewelina, Lewicki Romuald, Studnicki Rafał, Szłapińska Joanna, Kubicki Jacek, Włoch Anna, Opuchlik Anna. Ocena wpływu obozu pierwszego stopnia Aktywnej Rehabilitacji na jakość życia osób po uszkodzeniu rdzenia kręgowego w zależności od poziomu uszkodzenia rdzenia kręgowego = The influence of the first degree camp of Active Rehabilitation on life quality experienced by the persons after the spinal cord damage - depending on the level of the spinal cord damage. The research report. Journal of Education, Health and Sport. 2015;5(12):149-159. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35259 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A149-159 http://pbn.nauka.gov.pl/works/678819 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 10.12.2015. Ocena wpływu obozu pierwszego stopnia Aktywnej Rehabilitacji na jakość życia osób po uszkodzeniu rdzenia kręgowego w zależności od poziomu uszkodzenia rdzenia kręgowego The influence of the first degree camp of Active Rehabilitation on life quality experienced by the persons after the spinal cord damage - depending on the level of the spinal cord damage Ewelina Kamińska-Gwóźdź Instytut Fizjoterapii, Wydział Lekarski i Nauk o Zdrowiu, Uniwersytet Jana Kochanowskiego, Al. IX Wieków Kielc 19, Kielce Ewelina Kamińska-Gwóźdź Institute of Physiotherapy, Faculty of Medicine and Health Sciences, Jan Kochanowski University, Kielce Romuald Lewicki Katedra Fizjoterapii, Wydział Wychowania Fizycznego i Turystyki, Wszechnica Świętokrzyska, ul. E. Orzeszkowej 15, Kielce Romuald Lewicki The Department of Physiotherapy, Faculty of Physical Education and Tourism, Swietokrzyska Academy, Kielce Rafał Studnicki Zakład Fizjoterapii, Wydział Nauk o Zdrowiu z Oddziałem Pielęgniarstwa i Instytutem Medycyny Morskiej i Tropikalnej, Gdański Uniwersytet Medyczny, ul. Marii Skłodowskiej-Curie 3A, Gdańsk Rafał Studnicki The Unit of Physiotherapy, Faculty of Health Sciences Division of Nursing and the Institute of Maritime and Tropical Medicine, Medical University of Gdansk, Gdansk Joanna Szłapińska Zakład Kształcenia Ustawicznego i Doradztwa Zawodowego, Wydział Studiów Edukacyjnych, Uniwersytet im. Adama Mickiewicza, ul. Wieniawskiego 1, Poznań Joanna Szłapińska Department of Continuing Education and Vocational Guidance, Faculty of Educational Studies, Adam Mickiewicz University in Poznań Jacek Kubicki Gabinet Fizjoterapii i Pediatrii, ul. Edmunda Łopuskiego 19a, Kołobrzeg Jacek Kubicki Physiotherapy and Paediatrics Office, Kołobrzeg Anna Włoch Wyższa Szkoła Ekonomii, Prawa i Nauk Medycznych, Wydział Nauk Medycznych, Jagiellońska 109a, Kielce Anna Włoch High School of Economy, Law and Medical Sciences, Faculty of Medical Sciences Kielce Anna Opuchlik Świętokrzyskie Centrum Onkologii, Zakład Rehabilitacji, ul. Artwińskiego 3, Kielce Anna Opuchlik Rehabilitation Institute, The Holycross Cancer Center in Kielce, Kielce Słowa kluczowe: uszkodzenie rdzenia kręgowego, Aktywna Rehabilitacja, sport, Fundacja Aktywnej Rehabilitacji, Indeks Jakości Życia Ferrans i Powers, Test PIL, Test SONG. Keywords: spinal cord injury, Active Rehabilitation, sports, Foundation for Active Rehabilitation, Quality of Life Index, PIL Test, SONG Test. Streszczenie Wstęp. Uszkodzenia rdzenia kręgowego są jednymi z cięższych rodzajów niepełnosprawności powodują obniżenie jakości życia wpływając na psychikę chorego. Cel pracy. Ocena wpływu poziomu uszkodzenia rdzenia kręgowego na jakość życia po uczestnictwie w obozie pierwszego stopnia Aktywnej Rehabilitacji. Materiał i metody. Badana została grupa 100 osób po uszkodzeniu rdzenia kręgowego, przed uczestnictwem w obozie pierwszego stopnia Aktywnej Rehabilitacji oraz 3 miesiące po odbytym obozie. Uczestnikami badań były osoby pełnoletnie. Badając wykorzystano: Indeks Jakości Życia Ferrans i Powers Wersja III Ogólna (Polska), Test PIL, oraz Test SONG. Wyniki. Niezależnie od poziomu uszkodzenia rdzenia kręgowego, stwierdzono istotną poprawę w zakresie globalnej wartości Indeksu Jakości Życia, w podskali zdrowie i funkcjonowanie oraz psychologiczno-duchowej. W każdym z badanych poziomów uszkodzenia rdzenia poprawił się wynik w kategorii sens życia testu SONG. Wśród osób z uszkodzeniem rdzenia kręgowego w odcinku piersiowym i lędźwiowym istotne zmiany dotyczyły wartości globalnej testu PIL, oraz dwóch jego kategorii: afirmacja życia i ocena własnego życia. Zmiana charakterystyczna tylko dla osób z uszkodzeniem rdzenia kręgowego w odcinku piersiowym dotyczy kategorii: cele życia, sens życia, ocena siebie testu PIL oraz wyniku globalnego testu SONG i jego kategorii: ocena własnych dążeń. Zmianą charakterystyczną tylko dla uszkodzenia w odcinku lędźwiowym jest twórczy niepokój testu SONG. Wnioski. Najwięcej istotnych zmian w zakresie IJŻ, testów PIL i SONG na skutek pobytu na obozie Fundacji Aktywnej Rehabilitacji, stwierdzono wśród osób z uszkodzeniem rdzenia w odcinku piersiowym. Poziom uszkodzenia rdzenia kręgowego różnicuje poczucie sensu życia i motywację do podejmowania działań na rzecz jego poszukiwań po uczestnictwie w obozie Aktywnej Rehabilitacji. Summary Introduction. Spinal cord damages reduce the life quality and affect the patients’ psychological condition. The aim of the research: to determine the influence of the level of the spinal cord damage upon life quality after participation in the camp of Active Rehabilitation. Material and methods. The research group consisted of 100 persons (at least 18 years old) after the spinal cord damage. They were examined before the participation in the camp and then 3 months afterwards. The Quality of Life Index Ferrans and Powers – The Third General Version (Polish), the PIL Test and the SONG Test were applied. Results. In all the cases there was an improvement in the global value of the Quality of Life Index as well as in the category “meaning of life” in the SONG Test. For the persons with both the thoracic and lumbar spine damage the PIL Test results were improved – in the fields of life affirmation and self-assessment. The persons only with the thoracic spine damage reported positive changes in many categories in the PIL Test and in the global results of the SONG Test. For the people affected only by the lumbar spine damage the typical change was found in the “creative anxiety” category of the SONG Test. Conclusions. The largest number of changes in the tests results were revealed among the persons with the thoracic spine damage. The level of the spinal cord damage differentiates the perception of meaning of life and the motivation to take actions to seek it.